Fostering appropriate antibiotic use in a complex intervention: mixed-methods process evaluation alongside the cluster-randomized trial ARena - Poß-Doering, Regina; Kühn, Lukas; Kamradt, Martina; Stürmlinger, Anna; Glassen, Katharina; Andres, Edith; Kaufmann-Kolle, Petra; Wambach, Veit; Bader, Lutz; Szecsenyi, Joachim; Wensing, Michel (Antibiotics, 2020)
The cluster randomized trial ARena (sustainable reduction of antibiotic-induced antimicrobial resistance, 2017-2020) promoted appropriate use of antibiotics for acute non-complicated infections in primary care networks (PCNs) in Germany. A process evaluation assessed determinants of practice and explored factors associated with antibiotic prescribing patterns. This work describes its findings on uptake and impacts of the complex intervention program and indicates potential implementation into routine care. In a nested mixed-methods approach, a three-wave study-specific survey for participating physicians and medical assistants assessed potential impacts and uptake of the complex intervention program. Stakeholders received a one-time online questionnaire to reflect on network-related aspects. Semi-structured, open-ended interviews, with a purposive sample of physicians, medical assistants and stakeholders, explored program component acceptance for daily practice and perceived sustainability of intervention component effects. Intervention components were perceived to be smoothly integrable into practice routines. The highest uptake was reported for educational components: feedback reports, background information, e-learning modules and disease-specific quality circles (QCs). Participation in PCNs was seen as the motivational factor for guideline-oriented patient care and adoption of new routines. Future approaches to fostering appropriate antibiotics use by targeting health literacy competencies and clinician’s therapy decisions should combine evidence-based information sources, audit and feedback reports and QCs.
Gesehen am 17.02.2022